FUNDAMENTAL STUDY OF DECARBURIZATION BEHAVIOR OF LIQUID Fe-C DROPLETS IN OXIDIZING SLAG - Biswas, Jayasree (My University, 2021)
Bloating of metal droplets in emulsion is an important phenomenon in BOF steelmaking in controlling the kinetics of refining. This bloating controls the kinetics by mainly increasing the residence time (from ~¼th of a second to ~10-15 seconds) of the droplets in emulsion and the slag/metal surface (~5-6 times) area. The bloating behavior is determined by the decarburization kinetics. This work aims to develop fundamental understanding of the bloating phenomena through series of experiments and mathematical modeling to explore various factors affecting the kinetics of decarburization. An experimental study on varying the droplet carbon concentration, slag FeO concentration and basicity evidenced mixed controlled kinetics including transport of oxygen in the slag, interfacial (slag/metal) chemical reaction, nucleation and growth of CO bubbles. A mathematical model including these kinetic steps was developed. The model was able to demonstrate the partitioning of oxygen at the slag/metal interface into external (at the slag/metal interface) and internal (within droplet) decarburization in presence of the surface-active element sulfur. The model was developed using a single data set and validated for a wide range of experimental conditions. The model showed excellent agreement with experimental data for most of the reaction period but failed to predict a premature shutdown for droplets reacting with low conductivity slag. In order to understand this discrepancy, the slag ionic and electronic conductivity were varied which showed a premature shutdown of decarburization reaction with low conductivity slag and continuation of the reaction to the thermodynamic limit with high conductivity slag. A mechanism of generation of local electric field by accumulation of charge at the slag/metal interface was proposed to explain the premature shutdown of the reaction for low basicity slags. In all experiments with low conductivity slag sulfur was observed to delay the onset of internal decarburization. However, this effect was diminished or disappeared completely with high conductivity slag. This observation motivated additional experiments to study the competitive adsorption of oxygen and sulfur at the slag/metal interface both through experiments and modelling. It was shown that for low conductivity slag, sulfur poisoning inhibited reaction at the surface whereas for the high conductivity slags the faster transport of oxygen allowed oxygen to compete with sulfur for adsorption sites creating pathways for oxygen into the droplet. By including the possibility of competitive adsorption in the model it was possible to predict the behavior of high sulfur droplets in conductivity slags where the only modification to the model was to change the mass transfer coefficient as appropriate to the higher conductivity. Extension of this study to include silicon in the droplet showed significant effect on decarburization both in delaying bloating as well as increasing peak rate of decarburization.
This is a thesis includes both experimental and modeling studies for high temperature slag/metal reaction system.
Keywords: Steelmaking; Decarburization; Kinetics; Slag Conductivity; Adsoption; Desiliconization